Estudos e simulações ópticas sobre as linhas Ipê, Sapucaia e Quati - Custódio, Felipe de Souza (2022)
This report presents the studies and activities carried out by the student during his internship in the Optics Group of the National Synchrotron Light Laboratory. are exposed some necessary concepts about the theory that involves synchrotron radiation and the lines of light, relating such studies to the Physical Engineering course. It is also shown the methodology used, the OASYS and Spectra software and the programming language python. In sequence, the results obtained from simulations for the optimization of optical commissioning of the IPÊ, SAPUCAIA and QUATI lines. The code SHADOW ray-tracing was used to obtain the expected parameters of the beam when along the line, such as beam size and divergence, images of the beam at the positions of diagnostics, energy resolution and photon flux. Simulations were also carried out misalignment, which help in the identification of misaligned optical elements and verify how each degree of freedom of these elements affects the beam. The Spectra software was used for simulations of dipole or waver type sources, for flux calculations, beam brightness and size, magnetic field analysis, phase and fundamental energy. Per Lastly, the optical commissioning of the IPÊ line was monitored.